Industrial relations constructive dismissal - Yaacob, Samsudin (Universiti Putra Malaysia Press, 2013)
The constructive dismissal issue is not a new phenomenon though, unfortunately, few employers and employees fully understand it. This book was written based on research carried out by the author when he was the Chief Assistant Director of Industrial Relations at the Department of Industrial Relations Kuala Lumpur, Selangor and Penang. His personal experience as a practitioner of Industrial Relations contributed to the information provided in this book. The author has travelled widely researching the phenomena of constructive dismissal raised by employees and trade unions and discussing cases of constructive dismissal which have been decided by the Industrial Court. This book will thus be very useful to employers, in particular Human Resource Managers, Academics and Students and also as reference in the field of Industrial Relations for the general public.